'Smart city' concept in digital economics: practice of Russia and Kazakhstan. (3rd October 2022) - Turgel, Irina; Bozhko, Larisa; Ulyanova, Elizaveta
The article discusses approaches to smart city development in two post-Soviet countries - Russia and Kazakhstan. The features that both countries share are a large-sized public sector and the governments' use of direct economic regulation. The purpose of the study is to compare the national-level models of the governmental organisations in Russia and Kazakhstan in the context of smart city development. We describe the forms of state participation, in particular funding of national urban digitisation projects. We also compare the approaches to institutionalisation of the smart city concept in the light of national policies and the corresponding priority areas of these policies. As a result, this study sheds light on formal institutional practices and structures, key focus areas, and mechanisms of fund allocation in smart city development in Russia and Kazakhstan. The study relies on the research data of the project 'Enhancement of the State Regulation Policy for Intensifying Clusterization of Industrial Regions' supported by the Ministry of Education and Science of the Republic of Kazakhstan.